Thermographic Scan of the Thoracolumbar Area in Dogs with Acute Intervertebral Disc Extrusion (IVDE): A Retrospective Study - Cristian Zaha; Liliana Cărpinișan; Larisa Schuszler; Nistor Paula; Tudor Căsălean; Tiana Florea; Văduva Cristina; Bogdan Sicoe; Ciprian Rujescu; Roxana Dascălu (Life)
Background: several authors have documented variations in local temperature in both horses and dogs presenting acute intervertebral disc extrusion (IVDE) along the entire spinal column. However, none have demonstrated distinct temperature differences between healthy animals and those with IVDE. A retrospective study was conducted to assess the efficacy of thermography at evaluating local temperature and thermal patterns in healthy dogs as well in those with IVDE across the T11–L3 area. Methods: the study included 20 healthy dogs and 32 dogs with IVDE. For both groups of dogs, the thoracolumbar region was trimmed and, subsequently, scanned using the Flir E50 thermography device. The Flir Tool software was used to analyze three designated areas (Bx1, Bx2, Bx3) within the thoracolumbar region by comparing the average temperature of the minimum, maximum, and mean temperature recordings between the two groups. Results: the thermal pattern and the local temperature of the thoracolumbar area present differences between healthy dogs and those with IVDE. Conclusions: we recommend thermographic scanning of the thoracolumbar area to find differences in local temperature between healthy dogs and those with intervertebral disc extrusion. Further investigations are required to differentiate between disc extrusion that exhibits lateralization to the right or left.